De las rutas a las urnas. Intercambios y lealtades en el movimiento campesino paraguayo - Carlos M. Macías (Cahiers des Amériques Latines)
The Paraguayan peasant movement has as one of its main features the formation of political parties as useful tools for the movement. The peasant leaders are those who hegemonize these parties for the aims of the movement, keeping away any danger of instrumentalisation of social movements by parties. At the same time, an heterogeneous set of essential structures exist beyond the organizations in charge of the contentious mobilization. The peasant leaders face the challenge of articulation of this diversity of structures within the movement. The aim of this article is to explain certain strategies based on the intermediation between the state and the peasantry that leaders can use to try to capitalize its strength on contentious politics into electoral power. The current debates about patronage in politics and the arguments of some authors to question their relevance provide important clues to understand the strategies presented in this article. This reflections draw on observations made in Paraguay during a fieldwork where the theoretical questions were different. Nonetheless, the practical consequences of this subject were relevant enough to arise by themself.